Intraocular Pressure Profile After Trabeculectomy Surgery at Waled General Hospital 2022 - Najmi Fadhlurrohman; Intan Rahayu; Viora Piscaloka (Health & Medical Sciences, 2026)
This study aims to describe the intraocular pressure profile after trabeculectomy surgery at RSUD Waled during the period from January 1 to December 31, 2022. This study used an observational research design with a retrospective descriptive approach and a total sampling technique. Univariate data analysis was used to describe distribution of the results. A total of 66 patients underwent trabeculectomy surgery. The most common age group was early elderly (46-55 years) with 26 patients (39,4%). The majority were female (59,1%), and the most common diagnosis was primary open-angle glaucoma (POAG) with 30 patients (45,4%). The IOP profile after trabeculectomy showed that the majority achieved qualified success (IOP ≤21 mmHg with medication) in 48 patients (72,7%), followed by failure (IOP >21 mmHg) in 10 patients (15,2%), and complete success (IOP ≤21 mmHg without medication) in 8 patients (12,1%). Trabeculectomy surgery patients at Waled Hospital in 2022 based on type of glaucoma were found mostly POAG (primary open angle glaucoma with the most intraocular pressure achieving qualified success (IOP ≤21 mmHg with medication).